2020
DOI: 10.1093/ejcts/ezaa310
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fontan failure by classifying the severity of Fontan-associated liver disease: a single-centre cross-sectional study

Abstract: OBJECTIVES Fontan-associated liver disease (FALD) is a hallmark of the failing Fontan circulation, but no general classification of FALD severity exists. In this study, we propose a scoring system to grade the severity of FALD and analyse its applicability for evaluation of Fontan failure. METHODS From 2017 to 2019, a total of 129 successive Fontan patients received a comprehensive hepatic assessment. The FALD score was based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
1
12
0
1
Order By: Relevance
“…In a previous study, we proposed a scoring system (FALD score) to grade FALD severity based on a combination of laboratory parameters, hepatic ultrasound and transient elastography (TE). Our results revealed that the FALD score significantly correlated with Fontan hemodynamics and reliably discriminated between patients with and without Fontan failure ( 7 ). Liver-associated morbidity and mortality are well-described in the adult Fontan population and constitute major risk factors limiting survival after cardiac transplantation ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…In a previous study, we proposed a scoring system (FALD score) to grade FALD severity based on a combination of laboratory parameters, hepatic ultrasound and transient elastography (TE). Our results revealed that the FALD score significantly correlated with Fontan hemodynamics and reliably discriminated between patients with and without Fontan failure ( 7 ). Liver-associated morbidity and mortality are well-described in the adult Fontan population and constitute major risk factors limiting survival after cardiac transplantation ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 64%
“…The calculated Fibrotest® score was converted into liver fibrosis stages according to METAVIR histological classification for liver biopsies ( 11 ). The calculation of the FALD score has previously been described in detail ( 7 ). Briefly, scoring points assigned for each hepatic abnormality detected in the diagnostics mentioned above were summed up for the final FALD score ( 7 ).…”
Section: Methodsmentioning
confidence: 99%
“…This value appears higher than the conventional one established to define cirrhosis in cases with viral or metabolic etiology (>12 kPa), for the concurrent sinusoidal venous congestion that the liver undergoes post-Fontan. This assumption is supported by results of the literature obtained in dog and human experimental and clinic studies [8], which documented a significant increase in LS values by TE, only after 4 months since Fontan operation and that were predictive of advanced FALD with values above 20 kPa [10,23]. For this reason, it seems evident that the hemodynamic changes in the venous district after Fontan can determine organ damage, particularly with progressive liver fibrosis and cirrhosis over the years.…”
Section: Discussionmentioning
confidence: 74%
“…We have also concluded that if extracardiac and lateral tunnel connection Fontans are not comparable, then a single composite index, similarly constructed, may not be equally applicable to all. Recently, Schleiger et al 42 developing a composite index to test correlation with hepatic fibrosis scores. Rather than utilizing a variety of laboratory and testing values, we based our approach upon anatomical features that likely affect passive total cavopulmonary flow, specifically in those with extracardiac connections, the current eras most frequently performed connection.…”
Section: Discussionmentioning
confidence: 99%